Multi-objective optimization of processes for self-lubricating coating by laser cladding based on EWM-AMPSO algorithm and performance research - Shu, Linsen; Gong, Jiangtao; Wang, Xin (Journal of materials science, 2024)
The synergistic regulation of the cladding process and lubricating powder ratio is essential to enhance the quality of self-lubricating coatings. To systematically study the critical parameters for the preparation of Ni-based graphite self-lubricating composite coatings, the regression models between laser energy density, lubricating powder ratio, and overlap rate with shear strength and coefficient of friction were established by the BBD experimental model, and the effects of each parameter on the response were analyzed. Then, the optimal cladding parameters were solved with the EWM-AMPSO algorithm, and the reliability of the algorithm is proved by comparative verification method. Finally, the properties of the optimal coating were analyzed. The reason for the improved wear resistance and interfacial bonding properties of the coating was obtained to be the formation of enhanced phases, homogeneous microstructure and graphite, the lubricating film formed by wear, and good fracture toughness. Graphical abstract